STRATEGY FOR IMPROVING THE QUALITY OF DINE IN SERVICES AT MIE MAPAN RESTAURANT - Riesthandie; Nadlifatin, Reny; Krisprimandoyo, D. Agung (Universitas Nahdlatul Ulama Surabaya, 2024)
This study aims to measure service quality at Mie Mapan, especially during on-site dining, prove the relationship between service quality and repurchase intention and brand image, and determine the improvement strategies that need to be done. This study involved 145 customers of Mie Mapan restaurants in four branches, namely Mie Mapan Rungkut, Mie Mapan Barata, Mie Mapan Kusuma Bangsa and Mie Mapan MERR. The data obtained is then analyzed using SEM-PLS to prove the hypothesis. SERVQUAL and IPA methods are used to measure service quality and level of importance according to customers. Then the QFD method is used to determine the improvement strategy needed. The results of this study indicate that there is a significant influence between service quality on purchase intention, service quality on brand image, and brand image on purchase intention. This study also shows that the brand image variable is able to mediate the effect of service quality on purchase intention. The quality of service at Mie Mapan in the restaurant where the research was conducted is still considered low. There are four significant indicators to improve performance, namely: restaurant cleanliness, the appropriateness of cutlery, speed and accuracy of service and menu variations. The improvement strategy that needs to be done is to always renew cutlery regularly, check and monitor employee discipline, improve employee skills, provide facilities, and add menu variations.